Individuals' Motivation for Joining a Social Group: Examining Their Homogeneity. (March 2017) - Baber, Ruturaj; Upadhyay, Yogesh; Kaurav, Rahul Pratap Singh
Human, being a social animal, has desired to be part of a social group. The present study explores motives/reasons of an individual for joining a social group/club through surveys conducted at various cities of India. The result of data analysis suggests that individual desired to join social groups/clubs for self-development, social service, extraversion, social voracity, self and social gratification, and for emotional support. Furthermore, convergence in individuals was also explored on the basis of their responses. From the analysis, three clusters emerged, namely, inquisitive individuals, extrovert individuals and voracious individuals. The study also discusses the implications of the outcome for founders/managers/marketers of groups and researchers.